Vacinas recombinantes contra erisipela suína: desenvolvimento integrado de bioprocesso, da biologia molecular ao biorreator - Silva, Adilson José da (2011)
Swine erysipelas is among the diseases that causes great economic losses in swine cultures worldwide. The disease is caused by the bacterium Erysipelothrix rhusiopathiae, and the surface protein SpaA is one of its main antigens. Herein, we report studies concerning the development of recombinant vaccines against swine erysipelas based on the SpaA antigen. Protein production for a subunit vaccine formulation was studied in shaken flasks and 5.0 L bioreactors. For this propose, a 1026 bp fragment of the spaA gene was cloned in Escherichia coli cells under the lac promoter control. The recombinant organism (E. coli BL21(DE3) pET28a_spaA) was cultivated in fed batch using complex medium with glycerol as carbon source. Nonconventional induction strategies were evaluated and high protein yield (198 mgprot/gDCW) and productivity values (0.4 gprot/L.h) were reached. The same antigen was cloned for expression and secretion in attenuated Salmonella typhimurium cells to obtain a live bacterial vector for the SpaA antigen. The recombinant lineage was able to express and secrete the SpaA fragment fused to the alpha-hemolysin secretion signal both in vitro and in vivo. High plasmid maintenance was observed in both conditions. The vaccinal vehicle showed to be able to colonize the Peyer patches and to invade the gut epithelial barrier in the inoculated animals. Immunization tests in murine model showed that the recombinant antigen delivered by Salmonella cells inoculated by oral route induced the production of seric IgG antibodies anti-SpaA. According to the literature, these antibodies must be able to promote pathogen opsonization in case of infection, contributing to confer a protective immunity against swine erysipelas to the vaccinated animals. In summary, this work presents contributions to development of subunit vaccines against swine erysipelas, in the form of recombinant protein formulations, or SpaA antigen delivery by attenuated S. typhimurium cells.